THE INFLUENCE OF PHYSICAL AND NON-PHYSICAL WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE IN POSTGRADUATE UIN SUNAN AMPEL SURABAYA - Dwi Rosdiana; Sri Rahayu; Rifda Fitrianty; Christina Wulansari (LPSDI Bina Patria, 2025)
This study aims to analyze the impact of both physical and non-physical work environments on employee performance at the Graduate School of UIN Sunan Ampel Surabaya. The study uses a population of all employees at the Graduate School of UINSA. The sample was selected based on the criteria of employees who are currently active in the institution, and data was collected through a questionnaire from 38 respondents. The analytical technique used was multiple linear regression analysis with the aid of SPSS version 26 software, which involved validity testing, reliability testing, and classical assumption tests such as normality, multicollinearity, and heteroscedasticity tests. The results of the study show that the physical work environment has a significant effect on employee performance, and the non-physical work environment also significantly influences employee performance. A conducive work environment, both in terms of physical aspects like work facilities, and non-physical aspects such as relationships among employees and organizational culture, enhances productivity, concentration, and job satisfaction. By creating a work environment that is comfortable and aligned with employee needs, organizations can encourage better performance outcomes. The implications of this research contribute to the development of human resource management theory and provide strategic recommendations for creating a more productive work environment in higher education institutions.